7-year efficacy and safety of iStent inject trabecular micro-bypass in combined and standalone usage - Hengerer, Fritz; Auffarth, Gerd U.; Conrad-Hengerer, Ina (Advances in therapy, 2024)
Introduction: This study evaluated 7-year effectiveness and safety of second-generation trabecular micro-bypass implantation (iStent inject) either in combination with cataract surgery or as a standalone procedure (Combined or Standalone subgroups, respectively) in eyes with open-angle glaucoma. Methods: This prospective, non-randomized, unmasked, longitudinal study included 125 consecutive iStent inject cases of a single surgeon at a large German academic hospital. Patients had considerable preoperative disease burden, with mean intraocular pressure (IOP) of 23.5 mmHg, 84.8% of eyes on >= 2 medications, and 38.4% of eyes with prior glaucoma surgery. IOP, medications, adverse events, and secondary surgeries were assessed through 7 years in the Overall cohort and in Combined (n = 81) and Standalone (n = 44) subgroups. Results: Over 7-year follow-up, mean IOP decreased by 36.2-40.0% in Overall eyes, 34.1-38.9% in Combined eyes, and 39.5-43.5% in Standalone eyes (p < 0.001 at all timepoints for all groups). Meanwhile, mean medications decreased by 59.3-71.3% in Overall eyes, 57.9-69.0% in Combined eyes, and 62.1-76.2% in Standalone eyes (p < 0.001 at all timepoints in all groups). At last follow-up (mean 77.4 months; 92.8% of patients with last visit at 6 or 7 years), 83.7% of Overall eyes, 82.3% of Combined eyes, and 86.4% of Standalone eyes had achieved >= 20% IOP reduction vs preoperative. At last follow-up vs preoperative, 100% of eyes in all groups had the same or lower IOP and 100% had the same or lower medication regimen. Safety outcomes were favorable, with no filtration surgeries and only 4.84% of eyes experiencing clinically significant visual field loss over 7 years of follow-up. Conclusion: iStent inject implantation with or without phacoemulsification produced significant and durable 7-year reductions in IOP (similar to 34-44% reduction) and medications (similar to 58-76% reduction) while preventing filtering surgery in this cohort of patients with relatively high preoperative disease burden. Combined and Standalone cases had similarly favorable effectiveness and safety.